National representation: Ukrainian realities and prospects - Калюжний, Ростислав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Scientific review of the monograph of N. V. Zayats "National representation: the essence, subjects and implementation features in Ukraine."